INSTITUTIONAL FOUNDATIONS FOR THE DEVELOPMENT OF THE LOGISTICS SYSTEM IN AGRICULTURE - Bekzod, Djurayev; Chori, Kulmatov (Antis Publisher, 2024)
The channels of production and sale of agricultural products in Uzbekistan are a complex system. Organization of the flow of goods through the logistics system in the markets of agricultural products and the organization of a system of recycling of products after consumption, saving resources and reducing waste are one of the urgent issues. The main task of this study is to develop scientific foundations for solving the problems and opportunities of implementing a green supply chain in the organization of product flows. Taking into account the characteristics of the traditional logistics of agricultural products in Uzbekistan and the prospects for a green supply chain, measures for the development of agricultural product logistics and aspects of the quality and safety control system for agricultural products were developed on a scientific basis.